Systematic review and meta-analysis of the acute effects of self-selected rest intervals on exercise performance maintenance, lactate levels, and heart rate - LeTian Lv; Changxu Chen; Xuyang Liu; Huayang Liu; PanWen Wu (PLoS ONE, 2026)
Background Rest interval duration is a key variable in exercise prescription, influencing both performance and physiological responses. Traditional training typically employs fixed rest intervals; however, this approach may not adequately reflect individual variability in recovery needs. Recently, self-selected rest intervals—based on individual perception—have gained attention as a potential strategy for more precise load regulation. Nevertheless, current evidence regarding their effects on exercise performance, heart rate, and blood lactate remains inconsistent. Methods This study followed PRISMA guidelines and conducted a systematic search of Web of Science, PubMed, Cochrane Library, and Embase from database inception to March 20, 2026. Acute experimental studies comparing self-selected and fixed rest intervals were included. A three-level random-effects meta-analysis was performed to account for dependency among multiple effect sizes. Subgroup analyses, meta-regression, and sensitivity analyses were conducted to explore potential moderators and assess robustness. Results Sixteen studies (k = 16) involving 281 participants were included. No significant overall difference was observed between self-selected and fixed rest intervals for exercise performance (g = 0.27, 95% CI [−0.14, 0.69], p = 0.29), with substantial between-study heterogeneity. After removing outliers, a small but significant effect favoring self-selected rest intervals was identified (g = 0.20, 95% CI [0.08, 0.33], p < 0.01). No significant differences were observed for heart rate (g = 0.002, p = 0.98) or blood lactate (g = −0.20, p = 0.36). Conclusion Self-selected and fixed rest intervals produce comparable effects on exercise performance and physiological responses. However, self-selected rest intervals may confer a small advantage in maintaining performance under specific conditions. These findings should be interpreted with caution due to sensitivity to outliers and study heterogeneity.